Sorafenib-Induced Acute Pancreatitis - Saadati, Hamid; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Sorafenib BRAF labeled (Author: Nhevitt; Wikimedia Commons)